Experimental But Not Sex Differences of a Mental Rotation Training Program on Adolescents - Rodán, Antonio; Contreras, María José; Elosúa, M. Rosa; Gimeno, Patricia (Frontiers in Psychology, 2016)
Given the importance of visuospatial processing in areas related to the STEM (Science, Technology, Engineering, and Mathematics) disciplines, where there is still a considerable gap in the area of sex differences, the interest in the effects of visuospatial skills training continues to grow. Therefore, we have evaluated the visuospatial improvement of adolescents after performing a computerized mental rotation (MR) training program, as well as the relationship of this visuospatial ability with other cognitive, emotional factors and those factors based on the experience with videogames. The study, which was performed on students aged 14 and 15 years old, showed a significant improvement in this visuospatial skill for a training group (n = 21) compared to a control group (n = 24). Furthermore, no significant sex differences were obtained for spatial ability or for any of the other tasks evaluated, either before or after training. Regarding the relationship between skills, a significant correlation between experience with video games and spatial ability was found, as well as between mathematical reasoning and intelligence and with spatial ability in the initial phase for the total sample. These findings are discussed from a cognitive point of view and within the current sociocultural context, where the equal use of new technologies could help reduce the visuospatial gap between sexes.